PENGARUH SKARIFIKASI MENGGUNAKAN URIN KAMBING PADA BIJI GAMAL (Gliricida sepium) DENGAN WAKTU PERENDAMAN BERBEDA TERHADAP KUALITAS BENIH - Holil Pathan Nur; Agung Kusuma Wijaya; Liman Liman; Muhtarudin Muhtarudin (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the effect of scarification using goat urine with different soaking time on the quality of gamal seeds (Gliricidia sepium) and determine the best scarification treatment that produces normal sprouts and the best sprouts. This research was conducted in January 2020, located in the Laboratory of Animal Nutrition and Feed, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used an experimental method using Completely Randomized Design with 5 treatments (control or without soaking, seed soaking for 4, 8, 12, and 16 hours) and 6 replications. Each trial unit received 30 seeds of Gamal. Data analysis was performed using the ANOVA continued by the least significant difference (LSD) test. The results showed that scarification of gamal seeds in goat urine at different times of soaking gave significantly effect (P <0.05) on germination, normal sprouts, dead seeds and hard seeds, but did not affect on abnormal sprouts and yield attacked by pests. The best scarification treatment for normal sprouts and sprouts rate was soaking for 16 hours, namely 60.00% and 47.73%, respectively. This results showed the longer soaking the seeds, the higher the germination and normal sprouts. Keywords: Gamal seeds, Goat urine, Scarification, Soaking time